Angiopoietin 1 reduces rat follicular atresia mediated by apoptosis through the PI3K/Akt pathway - Parborell, Maria Fernanda Agustina (2011)
The aim of this study was to determine the effect of the local inhibition of ANGPT1 on steroid production, proliferation and apoptosis of ovarian follicular cells and on the PI3K/AKT pathway. We also examined the effect of ANGPTs on follicular cell apoptosis and proliferation in early antral follicles (EAFs) in culture. Follicular cells expressing PCNA decreased after ANGPT1 Ab treatment. Moreover, ANGPT1 inhibition increased the levels of active caspase 3 and androsterone, but decreased estradiol, AKT phosphorylation and the area of smooth muscle cell actin. In cultured EAFs from prepubertal rats treated with diethylstilbestrol (DES), ANGPT1 increased PCNA and decreased apoptosis while ANGPT2 reversed these effects. These results show that ANGPT1 alters steroidogenesis, reduces ovarian apoptosis, and stimulates cell proliferation in antral follicles. ANGPT1 may exert these roles by regulating ovarian vascular stability and/or by a direct effect on follicular cells, possibly involving the PI3K/AKT pathway.